Effect of HIV-infection on QuantiFERON-plus accuracy in patients with active tuberculosis and latent infection. Issue 5 (May 2020) - Petruccioli, Elisa; Chiacchio, Teresa; Navarra, Assunta; Vanini, Valentina; Cuzzi, Gilda; Cimaglia, Claudia; Codecasa, Luigi Ruffo; Pinnetti, Carmela; Riccardi, Niccolò; Palmieri, Fabrizio; Antinori, Andrea; Goletti, Delia
Highlights: QFT-Plus has similar sensitivity for active TB detection independently of HIV infection. CD4 count does not influence IFNγ values of QFT-Plus in HIV-TB patients. HIV-LTBI have high proportion of IFNγ values in the "uncertain range" of QFT-Plus. Impairment of CD4 response to QFT-Plus antigens in the HIV-infected subjects. Similar CD8 response to QFT-Plus antigens in HIV-infected and –uninfected subjects. Summary: Objective: HIV-infection increases the risk to progress to active-tuberculosis (TB). Detection of latent TB infection (LTBI) is needed to eventually propose preventive-therapy and reduce TB reservoir. QuantiFERON-TB Plus (QFT-Plus)-test identifies LTBI. Currently, only two studies on QFT-Plus accuracy in HIV-infected-population are available in high TB-endemic-countries. Therefore we aimed to evaluate the effect of HIV-infection on QFT-Plus accuracy to detect LTBI in a low TB-endemic-country. Methods: We enrolled 465 participants, among the 167 HIV-infected-persons: 32 with active-TB (HIV-TB), 45 remote-LTBI (HIV-LTBI) and 90 at low M. tuberculosis (Mtb)-infection risk. Among the 298 HIV-uninfected-persons: 170 with active-TB, 76 recent-LTBI, 34 remote-LTBI and 18 with low Mtb-infection risk. Results: QFT-Plus sensitivity was similar in TB regardless of HIV-status. CD4-count did not influence the distribution of IFN-γ values in HIV-TB and HIV-LTBI. Moreover HIV-LTBI and HIV-uninfected remote LTBI had a similar proportion of results in the uncertain range (IFNγ ≥0.2 ≤ 0.7 IU/ml) differently from those LTBI-persons reporting recent-exposure ( p  = 0.016). Cytometry results demonstrated that CD8-response was similar in HIV-infected- and -uninfected-persons whereas CD4-response was impaired in HIV-infected-persons ( p  = 0.011). Conclusions: HIV-infection does not affect QFT-Plus response in active-TB, whereas the time of exposure influences the proportion of uncertain-results in LTBI.